IMPLEMENTASI KERJA SAMA INDONESIA-UE DALAM PROYEK RETHINKING PLASTICS: STUDI KASUS DI KOTA TEGAL (2019–2022) - Rana Aghisna; Khoirunnisa Khoirunnisa (Pojok Publisher, 2025)
This study aims to analyze the implementation of the Rethinking Plastics Project (2019-2022) in Tegal City in the context of marine plastic waste management and its contribution to the development of Government and Political Science. The method used is a qualitative approach with a case study design, involving the Maritime Affairs & Fisheries Service of the Tegalsari Archipelago Fisheries Port, the Tegal Bahari Children's Forum (Fantri), and waste management businesses in coastal areas. Data were collected through document analysis and analyzed using the process tracing method. The results show that although the project succeeded in reducing the percentage of plastic waste significantly at the peak of the intervention, the reduction cannot be fully attributed to the project due to limited coverage and duration of implementation. Local policies such as restrictions on single-use plastics and increasing the capacity of TPS (landfill sites) also played a significant role. This study emphasizes the importance of cross-sectoral collaboration and the integration of local policies with bilateral initiatives for sustainable plastic waste management. Recommendations include the establishment of a coordination forum, the development of incentive schemes, the expansion of inclusive education, and the strengthening of the circular economy through budget support and technical training. The contribution of this study lies in understanding the dynamics of cooperation between local governments and non-state actors in sustainable environmental management.